2017
DOI: 10.4103/ccd.ccd_1109_16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three different sealer placement techniques: An In vitro confocal laser microscopic study

Abstract: Introduction:Three-dimensional obturation of the root canal system is the final objective of root canal therapy. Greater penetration of sealer in root dentine lesser will be the voids at the dentine–sealer interface. Hence, analysis of the dentin/sealer interface allows the determination of a filling technique which could obturate the root canals with least gaps and voids. Therefore, the aim of this study is to compare the depth and percentage of sealer penetration into root dentin using three different root c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…These effects frequently occur in the irrigants during passive ultrasonic irrigation. On the other hand, these findings are in disagreement with Dash et al 27 who used ultrasonic tip at lower power than that in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These effects frequently occur in the irrigants during passive ultrasonic irrigation. On the other hand, these findings are in disagreement with Dash et al 27 who used ultrasonic tip at lower power than that in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be attributed to the more efficient rotary motion of the lentulo spiral in a relatively wider cervical region where the smear layer is more effectively removed. Dash et al 27 reported that Lentulo spiral technique had a mean penetration depth and percentage higher than the ultrasonic technique because the lentulo spiral forces the sealer along the instrument length, whereas ultrasonic files move the sealer centrifugally.The intratubular sealer penetration findings showed that the activated Irrisafe ultrasonic tip performed better than lentulo spiral in the apical region in agreement with previous studies. 24,28 These findings might result from the transmission of acoustic microstreaming energy generated by the ultrasonic tip, which probably forced the sealer into these areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not possible to affirm that the differences in maximum depth values in the present review are related to these factors given that other factors, such as the use of a lentulo spiral, may interfere with the process. Lentulo has an action that pushes the sealer centrifugally (43), which could result in better sealer penetration compared with a master cone.…”
Section: Discussionmentioning
confidence: 99%
“…37 Confocal laser scanning microscope (CLSM) has been employed for evaluating the sealer penetration. [38][39][40] CLSM has several advantages, such as being able to use non-decalcified or hard tissue samples that do not require a specific sectioning technique (sputter coating), providing detailed information about the presence and distribution of sealers at relatively low magnification through the use of fluorescent rhodamine-marked sealers, and allowing the exclusion of artifacts from the sample. 38 In the present study, sealer penetration into root dentin was influenced by the irrigant used.…”
Section: Discussionmentioning
confidence: 99%